2021
DOI: 10.1038/s41586-021-03922-4
|View full text |Cite
|
Sign up to set email alerts
|

Biologically informed deep neural network for prostate cancer discovery

Abstract: The determination of molecular features that mediate clinically aggressive phenotypes in prostate cancer remains a major biological and clinical challenge1,2. Recent advances in interpretability of machine learning models as applied to biomedical problems may enable discovery and prediction in clinical cancer genomics3–5. Here we developed P-NET—a biologically informed deep learning model—to stratify patients with prostate cancer by treatment-resistance state and evaluate molecular drivers of treatment resista… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
175
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 220 publications
(208 citation statements)
references
References 49 publications
8
175
0
Order By: Relevance
“…For example, in the area of lung related complications, deep neural networks have been explored to great effect for aiding clinicians in the detection of tuberculosis ( 8 , 9 ), pulmonary fibrosis ( 10 , 11 ), and lung cancer ( 12 14 ). Similar works have been done for prostate cancer ( 15 , 15 , 16 ) and breast cancer ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 55%
“…For example, in the area of lung related complications, deep neural networks have been explored to great effect for aiding clinicians in the detection of tuberculosis ( 8 , 9 ), pulmonary fibrosis ( 10 , 11 ), and lung cancer ( 12 14 ). Similar works have been done for prostate cancer ( 15 , 15 , 16 ) and breast cancer ( 17 , 18 ).…”
Section: Introductionsupporting
confidence: 55%
“…The result indicates that the ensemble performance of gene-mWCA SVM (EGmWS) was regarded as effective methodology compared to related methodologies in terms of accuracy and solving the uncertainty problems. Elmarakeby et al [ 15 ] designed a P-NET—a biologically informed DL method—for stratifying patients with PCa by treatment resistance state and gauging molecular driver of treatment resistance to therapeutic target via method interpretability. They demonstrated that P-NET could forecast cancer state by utilizing molecular information with performances, i.e., better than other modeling techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…MDM4 suppresses p53 transcriptional activity and facilitates p53 proteasomal degradation via binding MDM2's E3 ligase activity towards p53 [505] . Overexpression of MDM4 has recently been detected in PCa tissue and increases with disease progression [506][507][508] . Recent transcriptomic characterization of MEX isolated from cow, donkey, and goat milk identified MDM4 as a central node protein for all three species, indicating a conserved checkpoint with higher numbers of interconnections [509] .…”
Section: Microrna-155 and Microrna-223mentioning
confidence: 99%